Mundos parecidos, mundos distintos - John H. Elliott (Mélanges de la Casa de Velázquez)
This article raises the question of how the Spanish saw the New World of America and its inhabitants, from the start of colonisation until the period of independence, starting with how the similarities and differences between the Old world and the New were seen. As they gradually came to regard America as a separate entity, an attempt was made to find reasons to explain the differences. Climatic determinism was an important part of these explanations. This stated that the natural humidity of the Indies had weakened its native inhabitants and had made them sluggish by temperament. Nevertheless, an environmental explanation also had serious implications for the Creole population subject, it was believed, to the same influences of heaven and earth. This study traces the reaction of the Creoles faced with allegations about their degeneracy caused by the environment in America, beginning with its insistence in its essential and inalienable Spanishness, until coming to recognise its «American» and therefore distinct character towards the end of the 18th century.